Viticulture–climate relationships in Greece: the impacts of recent climate trends on harvest date variation - George Koufos; Theodoros Mavromatis; Stefanos Koundouras; Nikolaos M. Fyllas; Gregory V. Jones (International Journal of Climatology, 2014)
Climate characteristics and relationships with indigenous varieties in Greece are examined to better understand how these varieties perform in their native climate and assess the impact regional climate change has on the Greek wine industry. Thus, harvest dates ( Δ H ) for eight indigenous varieties and regions, along with climate data, were gathered and systematically explored using linear regression models and principal component analysis for three ‘effective’ growing season time period definitions (calendar year, growing season and ripening period). The eight study regions had marked differences in their general climatic characteristics, mainly between mainland and island areas. Δ H response was not particularly sensitive to time period definition. In five out of eight regions, a systematic shift of Δ H was identified (earlier harvest), mainly driven by changes in maximum and minimum temperatures. Significant trends in climate parameters and viticulture–climate relationships were more evident for island regions when compared to mainland locations. Moreover, areas with late ripening varieties were shown to be less sensitive to climate changes. Only in one region harvest was delayed, possibly due to non‐climate factors. The identification of up‐to‐date climate and grapevine phenology relationships could be an important step for broader and more confident future assessments of climate suitability for viticulture and climate change impacts in Greece, and provide insights into how lesser known varieties might perform in other regions.